Ni doped CoSb3 nanostructured thermoelectric materials - Zhang, Lei (2010)
Researchers have renewed interests in high performance thermoelectric materials in recent years. New concepts and mechanisms have been published and tested, different new techniques to synthesize thermoelectric material have been developed; all these make it possible to achieve higher figure of merit (ZT) value for the next generation of thermoelectric materials, so that thermoelectric materials will become more competitive in the market for commercial applications such as peltier cooling or refrigeration applications and power generation in mediate and high temperature range. This project focused on the study of Ni doped CoSb3 n-type nanostructured. The sample pellets were prepared from nano powder by hot pressing. The nano powders were synthesized using a modified polyol method. Nano particles of Ni doped CoSb3 with different contents of Ni were prepared so that we could find the way to optimize the thermoelectric properties of Ni doped CoSb3 could be optimized. The general formula is NixCo(8-x)Sb24. The relationships between thermal conductivity, electrical conductivity and the amount of Ni elements doped into CoSb3 were discussed. The results obtained proved that Ni doped CoSb3 indeed show a higher electrical conductivity (lower electrical resistivity), and the same time, a minor increase in lattice thermal conductivity were also observed. At X= 1.25 in NixCo(8-x)Sb24, the highest ZT of 0.32 at temperature 730 K were observed which is big improvement compared with pure CoSb3 materials obtained by Spark plasma sintering, which is 0.095 at 673 K. However higher ZT values have been reported by newly developed methods such as low dimensional structuring of thermoelectric materials, ZT value over 1 were reported for Ni doped CoSb3, which is based on the technique of superlattice thin film.